Lithium secondary battery with improved safety

By using NCM-based positive electrode active material with high nickel (Ni) content in the positive electrode of the lithium secondary battery and adding cyclic ester solvents to the electrolyte composition, the problems of structural collapse and gas generation of lithium secondary battery at high temperatures are solved, and high energy density and safety are improved.

CN119563241APending Publication Date: 2025-03-04LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480003417.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2024-03-07
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing lithium secondary batteries have problems of structural collapse and gas generation at high temperatures, resulting in insufficient safety.

Method used

By using an NCM-based positive electrode active material with a high nickel (Ni) content in the positive electrode and adding more than 60% of the cyclic ester solvent to the electrolyte composition, the heat flow between the positive electrode active material and the electrolyte composition is maintained at 6.0 W/g or less in the range of 200°C to 300°C.

Benefits of technology

The energy density of lithium secondary batteries is improved, and the safety of the positive electrode active material at high temperatures is significantly improved, avoiding structural collapse and gas generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005243584050000021
    Figure BDA0005243584050000021
  • Figure BDA0005243584050000031
    Figure BDA0005243584050000031
  • Figure BDA0005243584050000042
    Figure BDA0005243584050000042
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery. The lithium secondary battery is advantageous in that the lithium secondary battery has excellent energy density by adding an NCM-based positive electrode active material having a high nickel (Ni) content to the positive electrode, and in that the lithium secondary battery has excellent energy density by controlling the heat flow between the positive electrode active material and the electrolyte composition at a low level within a predetermined range. The method has the effect of improving the safety problem of the positive electrode active material at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium secondary battery having a high energy density and improved high-temperature safety.

[0002] This application is based on and claims priority to Korean Patent Application No. 10-2023-0080465, filed on Jun. 22, 2023, the disclosure of which is incorporated herein by reference in its entirety. Background Art

[0003] Recently, secondary batteries have been widely used in small devices such as portable electronic devices and in large and medium-sized devices such as battery packs or power storage devices in hybrid vehicles or electric vehicles.

[0004] These secondary batteries are manufactured by coating a composition containing an electrode active material on a current collector with an appropriate thickness and length and then drying the composition; or by forming the electrode active material itself into a film to manufacture electrodes including a positive electrode and a negative electrode, and winding or laminating these electrodes with an insulating separator located therebetween to provide an electrode assembly. Then, the electrode assembly is placed in a can or a similar container and filled with an electrolyte, thereby manufacturing a secondary battery.

[0005] In order to apply secondary batteries to large and medium-sized devices, secondary batteries are required to have a high energy density. Therefore, by using a layered lithium nickel metal oxide having a nickel (Ni) content of more than 60% (for example, LiNi a Co b Mn c O2, 0.6 < a ≤ 0.9, a + b + c = 1, hereinafter referred to as "NCM-based compound") as a positive electrode active material, a high capacity of the secondary battery has been achieved.

[0006] [Prior Art Documents]

[0007] [Patent Documents]

[0008] Korean Patent Application Publication No. 10-2018-0116564

[0009] Korean Patent Publication No. 10-2144056 Summary of the Invention

[0010] [Technical Problem]

[0011] An object of the present invention is to provide a lithium secondary battery that has an improved energy density by adding an NCM-based positive electrode active material having a relatively high nickel (Ni) content to the positive electrode and has improved safety by improving structural collapse of the NCM-based active material at high temperatures or gas generation caused by the structural collapse.

[0012] [Technical Solution]

[0013] According to an embodiment of the present invention, a battery (e.g., a lithium secondary battery) includes:

[0014] an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; and

[0015] an electrolyte composition impregnating the electrode assembly,

[0016] wherein the positive electrode has a positive electrode active layer disposed on at least one surface of a positive electrode current collector, and the positive electrode active layer contains a lithium metal oxide represented by Formula 1 as an active positive electrode material;

[0017] wherein the electrolyte composition includes a lithium salt and a non-aqueous organic solvent, and based on the total weight of the non-aqueous organic solvent, the non-aqueous organic solvent includes 60% by weight or more of a cyclic ester solvent represented by Formula 2;

[0018] wherein when a heat flow measurement is performed on a mixture of the positive electrode active material and the electrolyte composition in a 100% charged state having a weight ratio of 1:1, the heat flow measured in a temperature range of 200 °C to 300 °C is 6.0 W / g or less:

[0019] [Formula 1]

[0020] Li x [Ni y Co z Mn w M 1 v O2

[0021] [Formula 2]

[0022]

[0023] In Formulas 1 and 2, M 1 is one or more elements selected from the group consisting of: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,

[0024] x, y, z, w, and v respectively satisfy 0.9 ≤ x ≤ 1.30, 0.6 ≤ y < 1, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and 0 ≤ v ≤ 0.1, provided that y + z + w + v = 1,

[0025] represents a single bond or a double bond,

[0026] X is hydrogen, fluorine, or vinyl; and

[0027] p is an integer from 1 to 5.

[0028] In this case, the positive electrode active material may include LiNi 0.95 Co 0.03 Mn 0.02 O2、LiNi 0.9 Co 0.6 Mn 0.4 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.85 Co 0.1 Mn 0.05 O2、LiNi 0.85 Co 0.05 Mn 0.1 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.75 Co 0.2 Mn 0.15 O2、LiNi 0.7 Co 0.2 Mn 0.1 O2、LiNi 0.7 Co 0.15 Mn 0.15 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2 and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 At least one of O2.

[0029] In addition, the cyclic ester-based solvent represented by Formula 2 may include one or more of dihydrofuranone, vinyldihydrofuranone, fluorodihydrofuranone, furanone, tetrahydropyrone, methyldihydrofuranone, propyltetrahydrofuranone, and oxepanone.

[0030] In addition, lithium salts may contain Li + as cation, and selected from BF4 - , B 10 Cl10 - 、ClO4 - 、AlO4 - 、AlCl4 - PF6 - 、SbF6 - 、AsF6 - 、BF2C2O4 - 、B(C2O4)2 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、(C2O4)2PF2 - CF3SO3 - 、C4F9SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - 、(CF3CF2SO2)2N - and ((C(CN))2NC(CF3))N - At least one anion.

[0031] In one embodiment, the lithium salt may contain Li + as cation, and selected from BF2C2O4 - 、B(C2O4)2 - 、(CF3SO2)2N - 、(FSO2)2N - 、(CF3CF2SO2)2N - and ((C(CN))2NC(CF3)N - anions in .

[0032] In other embodiments, the lithium salt may contain Li + as cation, and selected from BF4- , B 10 Cl 10 - 、ClO4 - 、AlO4 - 、AlCl4 - PF6 - 、SbF6 - 、AsF6 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、(C2O4)2PF2 - CF3SO3 - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - and SCN - At least two anions in the

[0033] In addition, the non-aqueous organic solvent further includes at least one auxiliary solvent selected from the group consisting of fluorinated ether solvents, fluorinated cyclic carbonate solvents, chain carbonate solvents, phosphate / ester solvents and sulfone solvents.

[0034] In addition, the electrolyte composition may further contain an electrolyte additive represented by Formula 3:

[0035] [Formula 3]

[0036]

[0037] Among them, R1 represents

[0038] R1' and R1" independently represent hydrogen or methyl,

[0039] R2 includes at least one of the following: an arylene group having 6 to 20 carbon atoms; an aryloxy group having 6 to 20 carbon atoms; a heteroarylene group having 5 to 10 carbon atoms and at least one heteroatom among N, S and O; a heteroaryloxy group having 5 to 10 carbon atoms and at least one heteroatom among N, S and O; an alkyl group having 1 to 10 carbon atoms; an alkyloxy group having 1 to 10 carbon atoms; a cycloalkyl group having 5 to 10 carbon atoms; and

[0040] R3 represents a fluoro group, an alkyl group having 1 to 10 carbon atoms, an alkyloxy group having 1 to 10 carbon atoms, or

[0041] Provided that the alkyl, alkyloxy, cycloalkyl, At least one hydrogen atom contained in may be replaced by a fluorine atom,

[0042] M comprises at least one selected from the group consisting of lithium, sodium, potassium, tetraalkylammonium having 1 to 4 carbon atoms, and tetraalkylphosphonium having 1 to 4 carbon atoms,

[0043] l is an integer from 1 to 6, and

[0044] m and n are each independently an integer of 2 to 20.

[0045] Specifically, the electrolyte additive represented by Formula 3 may contain one or more of the compounds represented by the following structural formulas 1 to 17:

[0046]

[0047] In this case, the electrolyte additive may be included in an amount of 5 wt % or less based on the total weight of the electrolyte composition.

[0048] At the same time, the negative electrode can be arranged on at least one side of the negative electrode collector and have a negative electrode active layer, which contains a carbon-based negative electrode active material and a silicon-based negative electrode active material, and the carbon-based negative electrode active material can contain at least one carbon material of natural graphite, artificial graphite, expanded graphite, hard carbon, acetylene black and Ketjen black.

[0049] In addition, the silicon-based negative electrode active material may include silicon (Si), silicon carbide (SiC), silicon oxide (SiO q , provided that at least one of 0.8≤q≤2.5) is present.

[0050] In this case, the content of the silicon-based negative electrode active material is 0.1 wt % to 30 wt % based on the total weight of the negative electrode active material.

[0051] In addition, in an exemplary embodiment, the present invention provides a method for manufacturing a lithium secondary battery, the lithium secondary battery comprising: an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; and an electrolyte composition impregnating the electrode assembly,

[0052] wherein the positive electrode includes a positive electrode active layer disposed on at least one surface of a positive electrode current collector and containing a lithium metal oxide represented by Formula 1 below as a positive electrode active material:

[0053] wherein the electrolyte composition includes a lithium salt and a non-aqueous organic solvent, and based on the total weight of the non-aqueous organic solvent, the non-aqueous organic solvent includes 60% by weight or more of a cyclic ester solvent represented by Formula 2;

[0054] wherein when measuring a mixture of the positive electrode active material and the electrolyte composition in a 100% charged state with a weight ratio of 1:1, the heat flow of the lithium secondary battery measured in a temperature range of 200°C to 300°C is 6.0 W / g or less:

[0055] [Formula 1]

[0056] Li x [Ni y Co z Mn w M 1 v O2

[0057] [Formula 2]

[0058]

[0059] In Formula 1 and Formula 2, M 1 is one or more elements selected from the group consisting of: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,

[0060] x, y, z, w, and v respectively satisfy 0.9 ≤ x ≤ 1.30, 0.6 ≤ y < 1, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and 0 ≤ v ≤ 0.1, provided that y + z + w + v = 1,

[0061] represents a single bond or a double bond, X is hydrogen, fluorine, or vinyl; and p is an integer from 1 to 5.

[0062] [Advantageous Effects]

[0063] The lithium secondary battery of the present invention has excellent energy density by adding NCM-based positive electrode active materials with high nickel (Ni) content in the positive electrode, and at the same time improves the safety problem of the positive electrode active material at high temperature by controlling the heat flow between the positive electrode active material and the electrolyte composition at high temperature to a lower level within a predetermined range. DETAILED DESCRIPTION

[0064] In the following detailed description, reference is made to the accompanying drawings, which form a part hereof.

[0065] However, the exemplary embodiments described in the detailed description, drawings, and claims are not meant to be limiting. Other embodiments may be used and other changes may be made without departing from the spirit or scope of the subject matter herein.

[0066] Terms such as “comprising” and “having” are intended to indicate the presence of the features, numbers, steps, operations, components and parts or a combination thereof described herein, but should not be interpreted as excluding the possibility of the presence or addition of one or more other features, numbers, steps, operations, components and parts or a combination thereof.

[0067] Furthermore, in the present invention, when a part of a layer, film, or plate is described as being "on" another part, it includes not only the case where it is "directly" "on" another part, but also the case where there is a part therebetween. Conversely, when a part of a layer, film, or plate is described as being "under" another part, it includes not only the case where it is "directly" "under" another part, but also the case where there is a part therebetween. Furthermore, in the present invention, being "on" may include being located below and above.

[0068] In addition, in the present invention, "containing ... as a main component" may refer to a specific component containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more) or 95% by weight or more (or 95% by volume or more) based on the total weight (or total volume). For example, "containing a carbon-based negative electrode active material as a main component" means that the content of the carbon-based negative electrode active material is 50% by weight or more, 60% by weight or more, 70% by weight or more or 80% by weight or more based on the total weight of the negative electrode active material. This may mean containing 90% by weight or more or 95% by weight of a carbon-based negative electrode active material, and in some cases, it may mean that the negative electrode active material is made of 100% by weight of a carbon-based negative electrode active material.

[0069] Since lithium secondary batteries have high energy density and excellent output performance, they are used as power sources for various electronic devices such as electric vehicles. In order to be used as power sources for such various electronic devices, electrochemical properties at high temperatures are required, and since the electrodes of lithium secondary batteries undergo an exothermic reaction with the electrolyte when exposed to high temperatures, it is important to have thermal stability.

[0070] NCM-based compounds are considered to be the best candidate materials to replace negative electrode active materials such as LiCoO2 due to their excellent overall properties, such as high capacity, high rate characteristics, good stability, and low cost, which also makes NCM-based compounds suitable for small, medium and large batteries. However, NCM-based compounds have the following disadvantages: such as low ionic conductivity, low cycle performance and tap density, complex manufacturing process, and when the proportion of nickel (Ni) is increased to achieve high capacity, the rate performance and capacity during charge and discharge are reduced.

[0071] The two main reasons for the decrease in electrochemical performance with increasing Ni content are side reactions and structural degradation. Among them, the side reaction refers to the reaction of lithium salts present on the surface of NCM-based compound particles used as positive electrode active materials with the electrolyte in the battery to form insulating materials on the surface of NCM-based compounds, or Ni 4+ ions accelerate the electrolyte decomposition to form a thick solid electrolyte interface (SEI) reaction. In addition, structural degradation refers to the reaction caused by Ni 2+ and Li + The structural degradation is caused by site exchange reactions (cation mixing) and structural changes (or collapse) of the layered structure due to oxygen loss caused by the escape of oxygen free radicals from the lattice. The limitation brought by structural degradation is that the migration of Li ions will be hindered during the charge and discharge process, resulting in reduced electrochemical characteristics. For example, when the structure of NCM-based active materials deteriorates at high temperatures, electrolyte decomposition occurs at the deteriorated site, and the oxidized carbon (CO or CO2) in the electrolyte decomposition process will produce water molecules in the process of combining with LiOH. These water molecules react with HF or LiF to produce a large amount of gas at a high speed inside the battery, causing the battery to explode, which is a problem that causes battery unsafety.

[0072] To address this problem, techniques for coating the surface of NCM-based compounds have been developed in the art. However, the limitations of surface coating are that an additional calcination process is required after the manufacture of NCM-based active materials, which increases the manufacturing cost, and it is difficult to obtain a uniform coating to effectively inhibit structural degradation.

[0073] Therefore, there is a need to develop a technology for improving the safety of a secondary battery by improving the energy density of a secondary battery by applying an NCM-based active material having a high nickel (Ni) content while suppressing structural degradation of the NCM-based active material at high temperatures.

[0074] The lithium secondary battery of the present invention has improved energy density by adding an NCM-based cathode active material with a high nickel (Ni) content to the cathode, and has improved the safety problem of the cathode active material at high temperatures by controlling the heat flow between the cathode active material and the electrolyte composition at a lower level within a predetermined range at high temperatures.

[0075] Hereinafter, the present invention will be described in more detail.

[0076] Lithium secondary battery

[0077] In one embodiment, the present invention provides a lithium secondary battery comprising:

[0078] an electrode assembly comprising a cathode, an anode, and a separator disposed between the cathode and the anode; and

[0079] an electrolyte composition impregnating the electrode assembly,

[0080] wherein the cathode has a cathode active layer disposed on at least one surface of a cathode current collector, and the cathode active layer contains a lithium metal oxide represented by Formula 1 as a cathode active material;

[0081] wherein, when measuring the heat flow of a mixture of the cathode active material and the electrolyte composition in a 100% charged state with a weight ratio of 1:1, the heat flow measured in the temperature range of 200 °C to 300 °C is 6.0 W / g or less:

[0082] [Chemical Formula 1]

[0083] Li x [Ni y Co z Mn w M 1 v O2(1)

[0084] In Formula 1, M 1 is one or more elements selected from the group consisting of: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,

[0085] x, y, z, w, and v respectively satisfy 0.9 ≤ x ≤ 1.30, 0.6 ≤ y < 1, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and 0 ≤ v ≤ 0.1, provided that y + z + w + v = 1.

[0086] The lithium secondary battery of the present invention includes: an electrode assembly having a structure in which a separator is disposed between a plurality of positive electrodes and a plurality of negative electrodes that are alternately stacked; and an electrolyte composition impregnated with the electrode assembly.

[0087] Here, the positive electrode in the electrode assembly includes a positive electrode active layer located on at least one side of a positive electrode collector, the positive electrode active layer is a material that can undergo an electrochemical reaction on the positive electrode collector to achieve electroactivity, and includes a lithium metal oxide represented by Formula 1 that can reversibly insert and release lithium ions as a main component.

[0088] The lithium metal oxide represented by Formula 1 is a composite oxide of lithium (Li) and transition metal elements including nickel (Ni), cobalt (Co) and manganese (Mn), wherein the content of nickel (Ni) is 60% or more (i.e., 60 mol% or more) based on the total molar number of the transition metal elements.

[0089] Ternary NCM-based negative electrode active materials based on nickel (Ni), cobalt (Co) and manganese (Mn) combine the advantages of high capacity of LiNiO2 (LNO), excellent electrochemical performance of LiCoO2 (LCO) and stability of LiMn2O4 (LMO). However, despite these advantages, as the nickel (Ni) content increases, cation mixing occurs, that is, the size and size of the cathode material change during the synthesis process and / or during charge and discharge under high temperature environment. Similar The phenomenon of forming a lithium layer with a layered structure. 2+ A Ni-O rock salt structure without local electrochemical reaction is formed, which hinders the migration of lithium ions, thus adversely affecting electrochemical properties such as high rate performance and discharge capacity. In addition, due to the unstable structure, when the secondary battery is charged and discharged under high temperature conditions, water molecules are generated as the electrolyte decomposes, which rapidly generate a large amount of gas inside the battery, so the high temperature safety of the secondary battery is limited.

[0090] However, the present invention uses the nickel metal oxide represented by Formula 1 as the positive electrode active material, wherein the nickel (Ni) content is more than 60% (i.e., more than 60 mol%) of the total molar number of transition metal elements, but reduces the heat flow between the positive electrode active material and the electrolyte composition at high temperature to meet the predetermined range. The present invention can solve this problem.

[0091] The term "heat flow" refers to the heat flow per unit weight, which can specifically indicate the degree of heat generation of a secondary battery. Compared with the electrolyte composition in the art, the electrolyte composition of the present invention can have higher thermal stability, and the thermal analysis results simulating the degradation phenomenon of the secondary battery due to high temperature exposure or external mechanical factors that spontaneously generates heat show that under high temperature conditions, there is a reaction difference between the positive electrode active material and the electrolyte composition, and the performance of the secondary battery decreases. For example, when simulating the high temperature degradation phenomenon of a secondary battery, the heat flow measured according to the thermal analysis results represents the degree of heat generation (e.g., heat) of the high temperature reaction between the electrolyte composition and the charged positive electrode active material.

[0092] The heat flow may increase or decrease depending on the type or content ratio of each component constituting the electrolyte composition, and may also increase or decrease depending on whether an inorganic positive electrode film containing lithium ions is formed on the surface of the positive electrode active layer. The decrease in heat flow indicates that the heat generated between the positive electrode active material and the electrolyte composition is reduced. Therefore, under high temperature conditions, the positive electrode active material contained in the secondary battery may be reduced due to i) Ni 2+ and Li + The layered structure undergoes a delayed structural change (or collapse) due to ii) the loss of oxygen caused by the site exchange reaction (cation mixing) and ii) the escape of oxygen radicals from the lattice.

[0093] At this time, in the range of 200°C to 300°C, the heat flow between the positive active material and the electrolyte composition of the present invention may be 6.0W / g or less. More specifically, the upper limit of the heat flow may be 5.5W / g or less, 5.0W / g or less, 4.0W / g or less, or 3.0W / g or less; the lower limit may be greater than 0W / g, 0.5W / g or more, 0.8W / g or more, 1.0W / g or more, or 2.0W / g or more. In one example, in the range of 200°C to 300°C, the heat flow between the positive active material and the electrolyte composition may be 0.5W / g to 6.0W / g, 0.5W / g to 5W / g, 0.5W / g to 4.5W / g, 0.5W / g to 4.0W / g, or 0.5W / g to 3.5W / g. Here, the heat flow can be calculated under predetermined conditions. Each material has a unique thermal conductivity constant, and the positive electrode active material and the electrolyte composition may also have different thermal conductivity constants. Due to this difference, the heat transferred between the positive electrode active material and the electrolyte composition may vary depending on the temperature conditions in which they are located. In other words, the heat flow between the positive electrode active material and the electrolyte composition will vary depending on the temperature conditions in which they are located. Therefore, the heat flow of the present invention can be measured under predetermined measurement conditions (specifically, the heating rate).

[0094] In one example, the heat flow between the positive electrode active material and the electrolyte composition can be measured using a differential scanning calorimeter (DSC) under the following conditions: the positive electrode active material and the electrolyte composition after being charged to 100% SOC at 4.25 V are mixed in a weight ratio of 1:1, and then measured in the range of 100°C to 400°C at a heating rate of 10±1°C / min.

[0095] In addition, the positive electrode active material may be used without limitation as long as the positive electrode active material is a lithium metal oxide represented by Formula 1, and more specifically, may include a lithium metal oxide selected from the group consisting of LiNi 0.95 Co 0.03 Mn 0.02 O2、LiNi 0.9 Co 0.6 Mn 0.4 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.85 Co 0.1 Mn 0.05 O2、LiNi 0.85 Co 0.05 Mn 0.1 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.75 Co 0.2 Mn 0.15 O2、LiNi 0.7 Co 0.2 Mn 0.1 O2、LiNi 0.7 Co 0.15 Mn 0.15 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2 and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 At least one of the group consisting of O2.

[0096] In addition, the electrolyte composition is a liquid electrolyte containing a lithium salt and a non-aqueous organic solvent. Here, the composition of the non-aqueous organic solvent can be adjusted so that the lithium salt and the non-aqueous organic solvent contain specific components to minimize the transfer of heat energy outside the secondary battery to the positive electrode active material inside the secondary battery.

[0097] For example, the nonaqueous organic solvent may contain a cyclic ester solvent represented by Formula 2 as a main component:

[0098] [Formula 2]

[0099]

[0100] In formula 2, represents a single bond or a double bond, X is hydrogen, fluorine or vinyl; and p is an integer from 1 to 5.

[0101] Specifically, the cyclic ester solvent represented by Formula 2 may include one or more of the following cyclic ester compounds:

[0102]

[0103] Generally, cyclic ester solvents (such as dihydrofuranone) have good lithium salt solubility, but when used with boron lithium salts (such as lithium bis(oxalato)borate (LiBOB, cation: Li + , anion: BF2C2O4 - )) or imide lithium salts, the cycle characteristics of the secondary battery are reduced, making it difficult to apply to lithium secondary batteries. However, in the present invention, by including an excess of the cyclic ester solvent represented by Formula 2 as a non-aqueous solvent in the electrolyte composition, when the lithium secondary battery is exposed to high temperatures, the transfer of external heat to the positive electrode active material is minimized. Therefore, the high temperature safety of the lithium secondary battery can be improved.

[0104] At this time, based on the total weight of the non-aqueous solvent of the electrolyte composition, the content of the cyclic ester solvent can be 60% by weight or more, such as 70% by weight or more, 75% by weight or more, 80% by weight or more, or 85% by weight or more, 90% by weight or more, 60% by weight to 99% by weight, 70% by weight to 99% by weight, 80% by weight to 99% by weight, 90% by weight to 99% by weight, 95% by weight to 99% by weight, 60% by weight to 80% by weight, or 70% by weight to 90% by weight. In some cases, the cyclic ester solvent itself can be used as a non-aqueous solvent, and the content is 100% by weight of the total weight of the non-aqueous solvent. By adjusting the content of the cyclic ester solvent contained in the non-aqueous solvent as described above, the present invention can avoid the following problems: when the content of the cyclic ester solvent is less than 60% by weight, the heat transferred to the positive active material during the high temperature exposure of the lithium secondary battery cannot be fully reduced. In addition, the cyclic ester solvent has excellent heat resistance. Therefore, when the content of the non-aqueous organic solvent is adjusted to the above range, the electrolyte composition is not easily decomposed at high temperatures. In addition, when used in combination with the lithium salt of the present invention, it is beneficial to minimize the amount of heat transferred to the positive electrode active material.

[0105] In addition, the electrolyte composition may contain a specific lithium salt to reduce the amount of heat transferred to the positive electrode active material. Specifically, the lithium salt may contain Li + As a cation, and containing BF4 - , B 10 Cl 10 - 、ClO4 - 、AlO4 - 、AlCl4 - PF6 - 、SbF6 - 、AsF6 - 、BF2C2O4 - 、B(C2O4)2 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、(C2O4)2PF2 - CF3SO3 - 、C4F9SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N -CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - 、(CF3CF2SO2)2N - and ((C(CN))2NC(CF3))N - At least one anion.

[0106] The lithium salt basically imparts conductivity to the organic solvent constituting the electrolyte, while inducing passivation of the negative electrode through the formation of SEI. In the present invention, the lithium salt is dissolved in the cyclic ester solvent, and when the lithium secondary battery is exposed to high temperature, the lithium salt decomposes on the positive electrode surface, thereby playing a role in delaying the structural degradation of the positive electrode active material. For this reason, the lithium salt used in the present invention may optionally include the above-mentioned lithium salt.

[0107] In one embodiment, the lithium salt may contain Li + As a cation, and containing BF2C2O4 - 、B(C2O4)2 - 、(CF3SO2)2N - 、(FSO2)2N - 、(CF3CF2SO2)2N - and ((C(CN))2NC(CF3))N - In this case, the lithium salt may contain a borate group or a sulfonamide group as an anion, thereby increasing the heat resistance of the electrolyte composition containing the lithium salt. In addition, the lithium salt contains a borate group or a sulfonamide group, so that a protective film can be formed by the reaction between the positive electrode active material and the electrolyte composition. Therefore, by delaying the structural degradation of the positive electrode, the effect of significantly reducing the heat flow rate can be achieved.

[0108] In another example, the lithium salt may contain Li + As a cation, and containing BF4 - , B 10 Cl 10 - 、ClO4 - 、AlO4 - 、AlCl4 - PF6 - 、SbF6 - 、AsF6 - PF4C2O4 -PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、(C2O4)2PF2 - CF3SO3 - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - and SCN - In this case, the lithium salt is used in the form of a double salt (i.e., a combination of different salts), thereby showing a synergistic effect to significantly improve the heat flow reduction effectiveness of the electrolyte composition, which is not obvious when used as a single component.

[0109] For example, LiPF6 releases PF6 upon dissociation - Anion, LiPF6 is a lithium salt commonly used in electrolyte compositions of lithium secondary batteries, and has the property of imparting high conductivity to carbonate electrolytes. However, when LiPF6 is used alone as a lithium salt, it decomposes into PF5 when exposed to high temperatures (e.g., above about 200°C). It is very unstable and removes the positive electrode film located on the surface of the positive electrode active layer and derived from organic substances (e.g., solvents) and positive electrode active materials, thereby reducing the high temperature durability of the positive electrode active material. However, LiBF4 decomposes into BF3 at temperatures above about 300°C, so its decomposition temperature is higher than the decomposition temperature of the positive electrode active material. That is, LiBF4 does not damage or remove the positive electrode film formed on the surface of the positive electrode active layer inside the secondary battery at high temperatures, so the high temperature durability of the positive electrode active material can be maintained. However, the effect of LiBF4 in improving the conductivity of the electrolyte composition is not obvious, and when the electrolyte containing LiBF4 is applied to a secondary battery, there is a limitation that the negative electrode performance is reduced. When applied alone to an electrolyte composition, LiPF6 and LiBF4 have limitations. However, when used together as a double salt as a lithium salt, LiPF6 and LiBF4 can achieve the effect of significantly improving the lower high temperature safety of LiPF6 and significantly reducing the heat flow of the electrolyte composition to the positive electrode active material.

[0110] In this case, when the lithium salt used in combination is a first lithium salt and a second lithium salt, the mixing ratio of the first lithium salt and the second lithium salt based on molar concentration can be 1:0.5 to 2.0, specifically 1:0.5 to 1.5, or 1:0.8 to 1.2. By adjusting the ratio of the first lithium salt and the second lithium salt forming the double salt as described above, the present invention can maximize the effect of reducing the heat flow of the electrolyte composition while minimizing the disadvantages of each lithium salt.

[0111] The concentration of these lithium salts is not particularly limited, but the lower limit of the preferred concentration can be above 0.5 mol / L, for example, above 0.7 mol / L or above 0.9 mol / L, and the upper limit can be below 2.5 mol / L, below 2.0 mol / L, or below 1.5 mol / L. When the lithium salt concentration is less than 0.5 mol / L, the ionic conductivity will decrease, which may reduce the cycle characteristics and output characteristics of the non-aqueous electrolyte battery. In addition, when the lithium salt concentration exceeds 2.5 mol / L, the viscosity of the electrolyte of the non-aqueous electrolyte battery increases, so the ionic conductivity will also decrease, which may reduce the cycle characteristics and output characteristics of the non-aqueous electrolyte battery.

[0112] In addition, when a large amount of lithium salt is dissolved in a non-aqueous organic solvent at one time, the liquid temperature may increase due to the heat of dissolution of the lithium salt. In the case of fluorine-containing lithium salts, when the temperature of the non-aqueous organic solvent increases significantly due to the heat of dissolution of the lithium salt, there is a risk of accelerated decomposition and formation of hydrogen fluoride (HF). Hydrogen fluoride (HF) can cause battery performance degradation and is therefore undesirable. Therefore, the temperature at which the lithium salt is dissolved in the non-aqueous organic solvent is not particularly limited, but can be adjusted between -20°C and 80°C, more particularly between 0°C and 60°C.

[0113] In addition, in addition to the above-mentioned ester solvents, the non-aqueous organic solvent may further include one or more auxiliary solvents selected from fluorinated ether solvents, fluorinated cyclic carbonate solvents, chain carbonate solvents, phosphate / ester solvents and sulfone solvents.

[0114] For example, the fluorinated ether solvent can be 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and the fluorinated cyclic carbonate solvent can be fluoroethylene carbonate (FEC). In addition, the chain carbonate solvent can be ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or diethyl carbonate (DEC), the phosphate / ester solvent can be trimethyl phosphate (TMP), and the sulfone solvent can be cyclopentane, methyl cyclopentane or dimethyl sulfoxide. In some cases, the non-aqueous organic solvent may also include a cyclic carbonate solvent, such as ethylene carbonate (EC).

[0115] The above-mentioned co-solvent can improve the low-temperature performance of the electrolyte composition and can have the effect of preventing the electrolyte composition from generating gas due to side reactions at high temperatures. Therefore, from the perspective of electrochemical stability to oxidation and reduction and chemical stability to heat or reaction with a solute, one type of co-solvent can be used alone in combination with the ester solvent, or two or more co-solvents can be used in any combination according to the purpose.

[0116] In addition, the cosolvent can be mixed with the ester solvent to meet a certain volume ratio. For example, based on the total volume of the non-aqueous organic solvent, the content of the cosolvent can be less than 40 volume %, more specifically, based on the total volume of the non-aqueous organic solvent, its content can be 30 volume % or less, 20 volume % or less, 1 volume % to 30 volume %, 1 volume % to 20 volume %, 1 volume % to 10 volume %, 5 volume % to 15 volume %, 5 volume % to 20 volume %, 10 volume % to 20 volume %, 20 volume % to 30 volume %, 1 volume % to 10 volume %, or 0.5 volume % to 5 volume %.

[0117] By adjusting the content of the co-solvent in the total non-aqueous organic solvent to the above ratio, the present invention can maintain high compatibility between the ester solvent and the co-solvent, and at the same time, improve the performance of the battery by increasing the charge mobility and / or ion mobility of the battery.

[0118] In addition, in order to reduce the viscosity of the electrolyte composition at 25 ° C and improve the compatibility of the ester solvent with the cosolvent represented by Formula 2, the non-aqueous organic solvent may be further mixed with an organic solvent for non-aqueous electrolytes in the art. At this time, based on the total weight of the non-aqueous organic solvent in the electrolyte composition, the content of the organic solvent may be less than 10 wt %. Examples of miscible non-aqueous organic solvents include aprotic organic solvents such as N-methyl-2-pyrrolidone, ethylene carbonate (EC), propylene carbonate, butylene carbonate, 1,2-dimethoxyethane (DME), tetrahydrofuran, 2-methyltetrahydrofuran, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, 1,3-dimethyl-2-imidazolidinone, ether, methyl pyrophosphate and ethyl propionate.

[0119] In addition to the above-mentioned essential components, the electrolyte composition may further contain additives. As long as the gist of the present invention is not impaired, commonly used additives may be added to the non-aqueous electrolyte of the present invention in any proportion.

[0120] Specifically, in combination with the non-aqueous organic solvent and the lithium salt, the electrolyte composition may further include an electrolyte additive represented by Formula 3:

[0121] [Formula 3]

[0122]

[0123] Among them, R1 represents

[0124] R1' and R1" independently represent hydrogen or methyl,

[0125] R2 includes at least one of the following: an arylene group having 6 to 20 carbon atoms; an aryloxy group having 6 to 20 carbon atoms; a heteroarylene group having 5 to 10 carbon atoms and at least one heteroatom among N, S and O; a heteroaryloxy group having 5 to 10 carbon atoms and at least one heteroatom among N, S and O; an alkyl group having 1 to 10 carbon atoms; an alkyloxy group having 1 to 10 carbon atoms; a cycloalkyl group having 5 to 10 carbon atoms; and

[0126] R3 represents a fluoro group, an alkyl group having 1 to 10 carbon atoms, an alkyloxy group having 1 to 10 carbon atoms, or

[0127] Provided that the alkyl, alkyloxy, cycloalkyl, At least one hydrogen atom contained in may be replaced by a fluorine atom,

[0128] M comprises at least one selected from the group consisting of lithium, sodium, potassium, tetraalkylammonium having 1 to 4 carbon atoms, and tetraalkylphosphonium having 1 to 4 carbon atoms,

[0129] l is an integer from 1 to 6, and

[0130] m and n are each independently an integer of 2 to 20.

[0131] As shown in Formula 3, the electrolyte additive contains an ionic compound with a parent core centered on a sulfonyl imide group, and is bonded to one side of the parent core with a vinyl group, a (meth) acrylate group or an acrylamide group through (i) a structure containing a saturated hydrocarbon group or a saturated hydrocarbon group having an oxygen atom; or (ii) a structure extending the conjugation of the sulfonyl imide group or having a polyethylene glycol unit.

[0132] The electrolyte additive has a chemical structure represented by Formula 3, so when the secondary battery is activated, an organic and / or inorganic film can be uniformly formed on the surface of the positive electrode and the negative electrode. That is, when the secondary battery is activated, the electrolyte additive can be directly contained in the organic and / or inorganic film formed on the surface of the positive electrode and / or the negative electrode in the form of a single molecule. Therefore, the electrolyte additive can inhibit the side reaction between the positive electrode and / or the negative electrode and the electrolyte composition, thereby improving the electrical performance of the secondary battery containing the electrolyte additive.

[0133] For this reason, in the compound represented by Formula 3,

[0134] R2 is ethylene, propylene, cyclohexylene, phenylene, methyleneoxy, pyrrole, phenyleneoxy, naphthyloxy, pyrroloxy, thienyleneoxy, pyranyloxy or

[0135] R3 is fluoro, methyl, fluoromethyl, methoxy, fluoromethoxy or The condition is At least one hydrogen atom contained in may be replaced by a fluorine atom,

[0136] M is lithium, l is an integer of 1 or 2, and m is an integer of 2 to 10.

[0137] In one example, the compound represented by Formula 3 may contain one or more of the compounds represented by the following structural formulas 1 to 17:

[0138]

[0139] Compared with positive electrode active materials such as lithium iron phosphate (LiFePO4), positive electrode active materials containing lithium metal oxides represented by formula 1 show higher potentials during charging and discharging. Therefore, when the electrolyte additives shown in structural formulas 1 to 17 are used in lithium secondary batteries together with positive electrode active materials such as lithium metal oxides represented by formula 1, during the activation process of the secondary battery, organic coatings and inorganic coatings can be uniformly formed on the positive and negative electrode surfaces, respectively, through the high charging and discharging potentials of the positive electrode active materials. When the secondary battery is exposed to high temperatures, the organic / inorganic coating formed in this way can effectively suppress the side reactions occurring in the electrolyte composition. In addition, the electrolyte additive can easily increase the oxidation potential window of the electrolyte composition, thereby preventing the electrolyte composition from decomposing during the charging and discharging of the secondary battery.

[0140] In one example, the electrolyte composition of the present invention may have an oxidation potential window of 4.5 V or more. More specifically, the oxidation potential window of the electrolyte composition may be 4.5 V to 7.0 V, 5.0 V to 6.5 V, 5.0 V to 6.0 V, 5.3 V to 6.5 V, or 5.5 V to 6.0 V.

[0141] The oxidation potential window refers to the voltage range within which no other electrochemical reactions occur in the secondary battery except the electrochemical redox reaction between the positive and negative electrodes. Here, Li / Li +The comparison value is used as a reference electrode. When the oxidation potential window of the electrolyte exceeds the above range, the potential window becomes narrower, so when the battery is charged and discharged, the non-aqueous electrolyte itself will undergo electrolysis, thereby shortening the service life of the lithium secondary battery and causing safety problems due to the generated gas. At the same time, when the electrolyte composition of the present invention meets the above oxidation potential window range, the electrolyte composition is stable relative to the potential applied during the charge and discharge process of the secondary battery, so the battery life can be improved and the risk of explosion can be reduced.

[0142] In addition, the electrolyte additive may be included in the electrolyte composition at a specific content. Specifically, based on the gross weight of the electrolyte composition, the content of the electrolyte additive comprising the compound represented by Formula 3 may be 5 wt % or less, specifically 0.01 wt % to 5 wt %. More specifically, based on the gross weight of the electrolyte composition, the content of the electrolyte additive may be 0.05 wt % to 3 wt % or 1.0 wt % to 2.5 wt %. The present invention can prevent the use of excessive electrolyte additives outside the above range from causing an increase in the viscosity of the electrolyte composition and thereby reducing the wettability of the electrode and the separator, while also preventing the ionic conductivity of the electrolyte composition from being reduced to reduce battery performance. In addition, the present invention also prevents the effect of the additive from being unobvious due to the use of trace electrolyte additives outside the above range.

[0143] The lithium secondary battery of the present invention includes the electrolyte composition, and thus can exhibit excellent high temperature stability even if a lithium metal oxide having a nickel (Ni) content of 60% or more in total mole is used as a positive electrode active material of the positive electrode.

[0144] Hereinafter, various components of the lithium secondary battery will be described in detail.

[0145] The electrode assembly provided in the lithium secondary battery of the present invention includes a positive electrode, a negative electrode and a separator.

[0146] In this case, the positive electrode includes a positive electrode active layer prepared by coating, drying, and pressing a positive electrode slurry containing a positive electrode active material on at least one surface of a positive electrode collector.

[0147] As described above, the positive active material contained in the positive active layer includes a lithium metal oxide having a nickel (Ni) content of 60% or more represented by Formula 1, and has the advantage of being able to stably supply high capacity power and / or high voltage power.

[0148] In addition, the content of the positive electrode active material may be 85 parts by weight or more, more specifically, 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the total weight of the positive electrode active layer.

[0149] Furthermore, if necessary, the positive electrode active layer may further contain a conductive material, a binder, and other additives in addition to the positive electrode active material.

[0150] In this case, the conductive material is used to improve the electrical properties of the positive electrode, and can be any material commonly used in the art. For example, the conductive material may include one or more selected from natural graphite, artificial graphite, carbon black, acetylene black, Denka black, Ketjen black, Super-P, channel black, furnace black, lamp black, summer black, graphene and carbon nanotubes.

[0151] In addition, based on the total weight of the positive electrode active layer, the content of the conductive material may be 0.1 to 5 parts by weight, in particular 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 0.5 to 3.5 parts by weight, 1 to 3 parts by weight, 0.1 to 2.5 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.

[0152] In addition, the role of the binder is to bind the positive active material, the positive electrode additive and the conductive material to each other, and any binder having this function can be used without particular limitation. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate and copolymers thereof. For example, the binder may include polyvinylidene fluoride (PVdF).

[0153] In addition, based on the total weight of the positive electrode active layer, the content of the binder may be 0.1 to 5 parts by weight, more specifically, 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 0.5 to 3.5 parts by weight, 1 to 3 parts by weight, 0.1 to 2.5 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.

[0154] The total thickness of the positive electrode active layer is not particularly limited, but may be specifically 50 to 300 μm, more specifically 100 to 200 μm, 80 to 150 μm, 120 to 170 μm, 150 to 300 μm, 200 to 300 μm, or 150 to 190 μm.

[0155] In addition, the positive electrode current collector may be a positive electrode current collector having high conductivity without causing chemical changes in the battery. Here, examples of positive electrode current collectors that can be used here may be stainless steel, aluminum, nickel, titanium or calcined carbon, and in the case of aluminum or stainless steel, those surface-treated with carbon, nickel, titanium or silver may also be used. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the current collector may be appropriately used in the range of 3 μm to 500 μm.

[0156] In addition, similar to the positive electrode, the negative electrode includes a negative electrode active layer prepared by coating, drying, and pressing a negative electrode slurry containing a negative electrode active material on at least one surface of a negative electrode collector.

[0157] According to the model or product application of the battery using the negative electrode of the present invention, the negative electrode active layer may have a structure in which two single layers are stacked, but is not limited thereto.

[0158] For example, the negative electrode of the present invention may have a structure in which a first negative electrode active layer is disposed on a negative electrode current collector, and a second negative electrode active layer is disposed on the first negative electrode active layer. In this case, the first negative electrode active layer and the second negative electrode active layer each contain a negative electrode active material, and the negative electrode active materials contained in each layer may be the same or different. When two layers of negative electrode active layers are disposed on the negative electrode current collector, the composition of each negative electrode active layer can be easily controlled, so that an active material with energy efficiency can be used as a negative electrode active material to improve the electrical properties of the negative electrode, and to improve and / or prevent problems arising therefrom (e.g., deterioration of the interfacial adhesion between the negative electrode current collector and the negative electrode active layer).

[0159] In addition, the negative electrode active layer contains a carbon-based negative electrode active material, thereby achieving electrical activity through a reversible redox reaction during the battery charge and discharge process.

[0160] The carbon-based negative electrode active material refers to a material containing carbon atoms as a main component, and the carbon-based negative electrode active material may include graphite. The graphite may include any one or more of natural graphite and artificial graphite.

[0161] In one example, the carbon-based negative electrode active material may include mixed graphite, which is a mixture of natural graphite and artificial graphite. In this case, the mixed graphite may be a mixture of natural graphite and artificial graphite in a weight ratio of 10 to 50:50 to 90, or 10 to 30:70 to 90. By adjusting the content ratio of natural graphite and artificial graphite as described above, the mixed graphite can prevent the adhesion of the negative electrode current collector and the negative electrode active layer from being reduced due to the total weight of natural graphite being less than 10 parts by weight, and can prevent the charge and discharge capacity of the negative electrode from being reduced due to the natural graphite being greater than 50 parts by weight.

[0162] In addition, the form of the carbon-based negative electrode active material is not particularly limited, but preferably a spherical graphite assembly formed by a plurality of flake graphites. In addition to natural graphite and artificial graphite, examples of flake graphite include those obtained by graphitizing mesophase calcined carbon (blocky mesophase) made of tar and pitch and coke (green coke, coarse coke, pitch coke, needle coke, petroleum coke, etc.). In particular, the carbon-based negative electrode active material is preferably a material assembled using a plurality of highly crystalline natural graphites. In addition, a graphite assembly can be formed by 2 to 100 sheets, preferably 3 to 20 sheets of flake graphite.

[0163] In addition, the average particle size (D 50 ) may be 0.5 μm to 20 μm. More specifically, the average particle size (D 50 ) may be 0.5 μm to 15 μm; 0.5 μm to 10 μm; 5 μm to 20 μm; 10 μm to 20 μm; 12 μm to 18 μm; 2 μm to 7 μm; 0.5 μm to 5 μm; or 1 μm to 3 μm.

[0164] It can be advantageous to make the average particle size of the carbon-based negative electrode active material smaller, so as to maximize the disorder of each particle in the expansion direction, thereby preventing the particles from expanding due to the charging of lithium ions. However, when the particle size of graphite is less than 0.5 μm, a large amount of binder may be required due to the increase in the number of particles per unit volume. At the same time, when the average particle size exceeds 20 μm, the expansion becomes severe, and when repeated charge and discharge, the cohesion between the particles and the adhesion between the particles and the current collector decrease, which may significantly reduce the cycle characteristics.

[0165] In addition, in addition to the carbon-based negative electrode active material, the negative electrode of the present invention may contain a predetermined silicon-based negative electrode active material in the negative electrode active layer. The silicon-based negative electrode active material is a material containing silicon (Si) as a main component, and may contain silicon (Si), silicon carbide (SiC), silicon monoxide (SiO) or silicon dioxide (SiO2) alone or in combination. When silicon monoxide (SiO) and silicon dioxide (SiO2) are uniformly mixed or combined as silicon-based negative electrode active materials and included in the negative electrode active layer, these components can be expressed as silicon oxide (SiO q , the condition is 0.8≤q≤2.5).

[0166] In addition, the negative electrode active material may be contained in an amount of 85 parts by weight or more, more specifically, 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the total weight of the negative electrode active layer.

[0167] In addition, based on the total weight of the negative electrode active material, the content of the silicon-based negative electrode active material may be 0.1% to 30% by weight, specifically 0.5% to 20% by weight, 1% to 9% by weight, 5% to 15% by weight, 3% to 7% by weight, 11% to 19% by weight, 13% to 17% by weight, 15% to 20% by weight, 10% to 30% by weight, 20% to 30% by weight, 15% to 25% by weight, or 9% to 22% by weight. By adjusting the content of the carbon-based negative electrode active material and the silicon-based negative electrode active material in the negative electrode active material to the above range, the present invention can improve the charging capacity per unit mass while reducing the lithium consumption and irreversible capacity loss during the initial charge and discharge process of the secondary battery. In addition, during the charging and discharging process of the secondary battery, by minimizing the volume change of the negative electrode active layer, the structural stability of the negative electrode active layer can be improved, thereby extending the life of the secondary battery.

[0168] Meanwhile, in addition to the carbon-based negative electrode active material as a main component, the negative electrode active layer of the present invention may optionally further include a conductive material, a binder, other additives, etc. as required.

[0169] The conductive material includes one or more types of carbon black, such as acetylene black and ketjen black; carbon nanotubes; and carbon fibers, but is not limited thereto.

[0170] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, or carbon fibers alone or in combination as the conductive material.

[0171] In this case, based on a total of 100 parts by weight of the negative electrode active layer, the content of the conductive material may be 0.1 to 10 parts by weight, more specifically, 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, or 0.5 to 2 parts by weight. The present invention controls the content of the conductive material within the above range, thereby suppressing the increase in negative electrode resistance and the resulting decrease in charging capacity due to the low content of the conductive material, and preventing the negative electrode active material content from decreasing due to excessive conductive material and the resulting decrease in charging capacity, or preventing the rapid charging characteristics from decreasing due to an increase in the load of the negative electrode active layer.

[0172] In addition, the binder can be appropriately used as a component that helps the negative electrode active material and the conductive material to adhere to the current collector without reducing the electrical properties of the electrode. Specific examples of binders may include any one or more selected from the following: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, poly(methyl methacrylate), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose (CMC), regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR) and fluororubber.

[0173] Based on a total of 100 parts by weight of the negative electrode active layer, the content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight. The present invention controls the content of the binder contained in the negative electrode active layer within the above range, thereby preventing the binding force of the active layer from being reduced due to a low content of the binder, or preventing the electrical characteristics of the electrode from being deteriorated due to an excessive amount of the binder.

[0174] Further, the average thickness of the negative electrode active layer can be 100 μm to 300 μm, more specifically, 100 μm to 250 μm, 100 μm to 250 μm; or 130 μm to 190 μm, and the average thickness can be the same as the average thickness of the flat area. By adjusting the average thickness of the negative electrode active layer to the above range, the present invention can make the crystal planes of the carbon-based negative electrode active material contained in each area uniformly arranged, thereby improving the high-rate charge and discharge performance and energy density of the battery containing the negative electrode.

[0175] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery, and examples thereof include copper, stainless steel, nickel, titanium, and calcined carbon. In the case of copper or stainless steel, those whose surfaces have been treated with carbon, nickel, titanium, silver, etc. may also be used. In addition, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the current collector may be appropriately 1 μm to 500 μm.

[0176] At the same time, the separator disposed between the positive electrode and the negative electrode of each unit cell is an insulating film with high ion permeability and mechanical strength, as long as it is commonly used in the art, there is no particular limitation, but specific examples thereof include separators containing one or more polymers selected from polypropylene, polyethylene, and polyethylene-propylene copolymers having chemical resistance and hydrophobicity. The separator may be in the form of a porous polymer substrate, such as a sheet or non-woven fabric containing the above polymer. In some cases, the separator may also be in the form of a composite separator in which organic or inorganic particles are coated on a porous polymer substrate using an organic binder. In addition, the average pore size of the separator may be 0.01 μm to 10 μm, and the average thickness may be 5 μm to 300 μm.

[0177] Meanwhile, the lithium secondary battery of the present invention is not particularly limited, and may be cylindrical, angular, pouch, or coin-shaped according to the intended use. The lithium secondary battery of the embodiment of the present invention may be a pouch-shaped secondary battery.

[0178] Method for preparing secondary battery

[0179] Furthermore, in an exemplary embodiment, the present invention provides:

[0180] A method for manufacturing a lithium secondary battery, the lithium secondary battery comprising: an electrode assembly comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; and an electrolyte composition impregnated with the electrode assembly,

[0181] The positive electrode comprises a positive electrode active layer, which is disposed on at least one side of the positive electrode current collector and contains a lithium metal oxide represented by the following formula 1 as a positive electrode active material;

[0182] Wherein, the electrolyte composition comprises a lithium salt and a non-aqueous organic solvent, and the non-aqueous organic solvent comprises 60 wt % or more of a cyclic ester solvent represented by Formula 2 based on the total weight of the non-aqueous organic solvent;

[0183] wherein, when a heat flow measurement is performed on a mixture of 100% of the positive electrode active material and the electrolyte composition in a charged state containing a weight ratio of 1:1, the heat flow measured in the range of 200° C. to 300° C. is 6.0 W / g or less;

[0184] [Formula 1]

[0185] Li x [Ni y Co z Mn w M 1 v ]O2

[0186] [Formula 2]

[0187]

[0188] In Formulas 1 and 2, M 1 is one or more elements selected from the group consisting of: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,

[0189] x, y, z, w, and v respectively satisfy 0.9 ≤ x ≤ 1.30, 0.6 ≤ y < 1, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and 0 ≤ v ≤ 0.1, provided that y + z + w + v = 1,

[0190] represents a single bond or a double bond, X is hydrogen, fluorine, or vinyl; and p is an integer from 1 to 5.

[0191] The method for manufacturing a lithium secondary battery of the present invention refers to the method for manufacturing the lithium secondary battery of the present invention described above. The method includes the step of impregnating an electrode assembly with an electrolyte composition, the electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The advantage of the electrode assembly is that the positive electrode of the electrode assembly includes an NCM-based positive electrode active material with a high nickel (Ni) content, and the electrolyte composition has the effect of reducing the heat flow rate between the positive electrode active material and the electrolyte composition at high temperatures to a predetermined range, thereby improving the safety problems caused to the positive electrode active material at high temperatures.

[0192] The specific descriptions of the positive electrode active material and the electrolyte composition are the same as those described above, and thus the specific descriptions are omitted.

[0193] Hereinafter, the present invention will be described in more detail through examples and experimental examples.

[0194] However, the following examples and experimental examples are only for describing the present invention, and the content of the present invention is not limited to the following examples and experimental examples.

[0195] Preparation Examples 1 to 17. Preparation of Electrolyte Compositions for Lithium Secondary Batteries

[0196] As non-aqueous solvents, dihydrofuranone (DHF), ethylene carbonate (EC), and ethyl methyl carbonate (EMC) were prepared, and as lithium salts, LiPF6, LiBF4, LiN(FSO2)2, and LiBF2(CO2)2 were prepared.

[0197] Each prepared lithium salt was dissolved in a non-aqueous organic solvent at a concentration of 1.0 M (≈1.0 mol / g) at 30° C. to 40° C., and an electrolyte additive was added in an amount of 2.0 wt % based on the total weight of the electrolyte composition to prepare an electrolyte composition. The composition of the non-aqueous organic solvent, the lithium salt, and the type of the electrolyte additive used herein are shown in Table 1 below.

[0198] [Table 1]

[0199]

[0200] Examples 1 to 8 and Comparative Examples 1 to 9. Preparation of lithium secondary batteries

[0201] Prepare LiNi with a particle size of 5 μm 0.86 Co 0.05 Mn 0.07 Al 0.02 O2 was used as the positive electrode active material and mixed with a carbon-based conductive material and polyvinylidene fluoride as a binder in a weight ratio of 94:3:3 in N-methylpyrrolidone (NMP) to prepare a positive electrode slurry with a solid content of 45%. The prepared positive electrode slurry was cast on a thin aluminum plate, dried in a vacuum oven at 120°C, and then rolled to prepare a positive electrode with a positive electrode active layer with a thickness of 160 μm.

[0202] In addition, a carbon-based negative electrode active material (composed of natural graphite and artificial graphite, with a weight ratio of 3:7) and a silicon-based negative electrode active material (containing SiO2) were mixed in a weight ratio of 88:12 to prepare a negative electrode active material. 97 parts by weight of the prepared negative electrode active material and 3 parts by weight of styrene-butadiene rubber (SBR) were mixed with water to prepare a negative electrode slurry with a solid content of 40%. The negative electrode slurry was cast onto a copper sheet, dried in a vacuum oven at 130°C, and then rolled to prepare a negative electrode having a negative electrode active layer with a thickness of 180 μm.

[0203] A separator made of 18 μm polypropylene was disposed between the positive electrode and the negative electrode, inserted into the outer case, and then the electrolyte composition prepared in the preparation example was injected as shown in Table 2 below, thereby assembling a lithium secondary battery.

[0204] Each assembled lithium secondary battery was initially charged. Specifically, the lithium secondary battery was initially charged to a charge end voltage of 4.2 V at 55±2° C. under the conditions shown in Table 2 below to produce an activated lithium secondary battery.

[0205] [Table 2]

[0206] Electrolyte composition type Example 1 Preparation Example 1 Electrolyte Composition Example 2 Preparation Example 2 Electrolyte Composition Example 3 Preparation Example 3 Electrolyte Composition Example 4 Preparation Example 4 Electrolyte Composition Example 5 Preparation Example 5 Electrolyte Composition Example 6 Preparation Example 6 Electrolyte Composition Example 7 Preparation Example 7 Electrolyte Composition Example 8 Preparation Example 8 Electrolyte Composition Comparative Example 1 Preparation Example 9 Electrolyte Composition Comparative Example 2 Preparation Example 10 Electrolyte Composition Comparative Example 3 Electrolyte composition of Preparation Example 11 Comparative Example 4 Preparation Example 12 Electrolyte Composition Comparative Example 5 Electrolyte composition of Preparation Example 13 Comparative Example 6 Electrolyte composition of Preparation Example 14 Comparative Example 7 Electrolyte composition of Preparation Example 15 Comparative Example 8 Preparation Example 16 Electrolyte Composition Comparative Example 9 Preparation Example 17 Electrolyte Composition

[0207] Experimental example

[0208] In order to evaluate the safety and charge / discharge performance of the lithium secondary battery of the present invention, the following experiments were conducted.

[0209] 1) Measure the heat flow between the positive electrode active material and the electrolyte composition

[0210] For each lithium secondary battery prepared in the embodiment and the comparative example, the lithium secondary battery was fully charged to 4.25 V at a rate of 0.5 C under constant current (CC)-constant voltage (CV) conditions at 25° C., and then the fully charged lithium secondary battery was disassembled, and the positive electrode active material LiNi 0.86 Co 0.05 Mn 0.07 Al 0.02 O2 and electrolyte composition and mix them.

[0211] The prepared mixture was injected into a sample tank of a differential scanning calorimeter (DSC) to prepare a sample, and the heat flow of the prepared sample was measured. In this case, the heat flow was measured in the range of 100°C to 350°C while increasing the temperature at a heating rate of 10±0.1°C / min.

[0212] According to the measurement results, the heat flow between the positive electrode active material and the electrolyte composition contained in each lithium secondary battery was evaluated, and when the measurement results had two or more effective heat flow peaks in the temperature range of 100°C to 350°C, the value of the peak with the maximum heat flow was determined as the corresponding heat flow. The results are shown in Table 3 below.

[0213] 2) Thermal runaway test evaluation

[0214] The lithium secondary batteries prepared in the examples and comparative examples were each charged at 25° C. under a constant current (CC) condition of 1.25 A until reaching 4.2 V, and then maintained at 4.2 V. After charging was completed, the lithium secondary batteries were activated by discharging to 2.85 V under a constant current (CC) condition of 1.25 A. Then, each activated lithium secondary battery was left to stand at 25° C. for 6 hours.

[0215] Then, the lithium secondary battery was fully charged to 4.2V at 25°C under a constant current (CC) condition maintained at 1.25A, and a thermal runaway test was performed using an accelerating calorimeter (ARC). At this time, the accelerating calorimeter (ARC) was obtained from THT (Thermal Hazard Technology), and the thermal runaway test was performed using the heating-waiting-searching (HWS) method. In the heating-waiting-searching (HWS) method, the temperature of the insulated oven containing each lithium secondary battery was heated from 50°C to 190°C by increasing 5°C at a rate of 10°C / min and waiting for 10 minutes. Here, when each lithium secondary battery waits for 10 minutes at an elevated temperature, if the lithium secondary battery has a temperature change of more than 0.02°C / min, it is confirmed that self-heating corresponding to thermal runaway (TR) is in progress, and from this point on, no additional heat energy is applied, thereby changing the temperature by means of the self-heating of each secondary battery. After the secondary battery self-heats, the self-heating curve of the secondary battery is measured, and the maximum temperature of the secondary battery is calculated based on the measured self-heating curve. The results are shown in Table 3 below.

[0216] [Table 3]

[0217] Heat flow [W / g] Maximum temperature during thermal runaway test [℃] Example 1 2.5±0.1 251.7 Example 2 2.4±0.1 253.2 Example 3 2.6±0.1 247.0 Example 4 2.7±0.1 254.5 Example 5 4.9±0.1 271.8 Example 6 2.9±0.1 258.8 Example 7 3.0±0.1 260.3 Example 8 3.5±0.1 272.1 Comparative Example 1 6.5±0.1 451.7 Comparative Example 2 6.8±0.1 319.5 Comparative Example 3 7.0±0.1 323.6 Comparative Example 4 7.2±0.1 468.6 Comparative Example 5 7.0±0.1 299.9 Comparative Example 6 7.4±0.1 324.9 Comparative Example 7 7.7±0.1 337.4 Comparative Example 8 30.5±0.2 513.8 Comparative Example 9 7.9±0.1 347.2

[0218] It can be found that although the lithium secondary battery of the present invention contains an NCM-based positive electrode active material with a high nickel (Ni) content (more than 80% of the total molar number of transition metal elements) in the positive electrode, it still has excellent high temperature safety and battery life by controlling the heat flow between the positive electrode active material and the electrolyte composition within a predetermined range.

[0219] For example, in the thermal runaway test, the lithium secondary batteries in the examples in which the heat flow between the positive electrode active material and the electrolyte composition was 6 W / g or less showed a lower maximum temperature of less than about 275°C.

[0220] Meanwhile, the lithium secondary battery of the comparative example, in which the heat flow between the positive electrode active material and the electrolyte composition exceeded 6 W / g, showed a high maximum temperature of about 299° C. or more in the thermal runaway test.

[0221] This indicates that when the heat flow between the positive electrode active material and the electrolyte composition is adjusted below a predetermined range, even for NCM-based active materials with a high nickel (Ni) content and low structural stability at high temperatures, damage to the positive electrode (e.g., structural degradation) can be suppressed and a significant increase in the temperature of the secondary battery at high temperatures can be prevented.

[0222] From the above results, it is found that the lithium secondary battery of the present invention has excellent energy density by adding an NCM-based positive electrode active material with a high nickel (Ni) content in the positive electrode, and improves the safety problem of the positive electrode active material at high temperature by controlling the heat flow between the positive electrode active material and the electrolyte composition to a lower level within a predetermined range.

[0223] From the foregoing, it should be understood that the various embodiments of the present invention are only for illustrative purposes, and various modifications may be made without departing from the scope and spirit of the present invention.

[0224] Accordingly, the various embodiments disclosed herein are not intended to be limiting, with the true scope and spirit being indicated by the following claims.

Claims

1. A secondary battery, comprising: An electrode assembly, the electrode assembly comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; and An electrolyte composition impregnating the electrode assembly, in, The positive electrode has a positive electrode active layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active layer contains a lithium metal oxide represented by Formula 1 as a positive electrode active material; Wherein, the electrolyte composition comprises a lithium salt and a non-aqueous organic solvent, and based on the total weight of the non-aqueous organic solvent, the non-aqueous organic solvent comprises 60% by weight or more of a cyclic ester solvent represented by Formula 2; Wherein, when a heat flow measurement is performed on a mixture of the positive electrode active material and the electrolyte composition in a 100% charged state with a weight ratio of 1:1, the heat flow measured in the temperature range of 200 °C to 300 °C is 6.0 W / g or less; [Formula 1] Li x [Ni y Co z Mr w M 1 v ]O2 [Formula 2] In Formula 1 and Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, x, y, z, w, and v respectively satisfy 0.9 ≤ x ≤ 1.30, 0.6 ≤ y < 1, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and 0 ≤ v ≤ 0.1, provided that y + z + w + v = 1, represents a single bond or a double bond, X is hydrogen, fluorine, or vinyl; and p is an integer from 1 to 5.

2. The secondary battery according to claim 1, wherein The positive electrode active material includes LiNi 0.95 Co 0.03 Mn 0.02 O2、LiNi 0.9 Co 0.6 Mn 0.4 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.85 Co 0.1 Mn 0.05 O2、LiNi 0.85 Co 0.05 Mn 0.1 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.75 Co 0.2 Mn 0.15 O2、LiNi 0.7 Co 0.2 Mn 0.1 O2、LiNi 0.7 Co 0.15 Mn 0.15 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2 and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 At least one of O2.

3. The secondary battery according to claim 1, wherein The cyclic ester solvent represented by Formula 2 contains one or more of dihydrofuranone, vinyl dihydrofuranone, fluorinated dihydrofuranone, furanone, tetrahydropyranone, methyl dihydrofuranone, propyl tetrahydropyranone, and oxepanone.

4. The secondary battery according to claim 1, wherein The lithium salt contains Li + As a cation, and containing BF4 - , B 10 Cl 10 - 、ClO4 - 、AlO4 - 、AlCl4 - PF6 - 、SbF6 - 、AsF6 - 、BF2C2O4 - 、B(C2O4)2 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、(C2O4)2PF2 - ,CF3SO3 - 、C4F9SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - 、(CF3CF2SO2)2N - and ((C(CN))2NC(CF3))N - At least one anion.

5. The secondary battery according to claim 1, wherein The lithium salt contains Li + As a cation, and containing BF2C2O4 - 、B(C2O4)2 - 、(CF3SO2)2N - 、(FSO2)2N - 、(CF3CF2SO2)2N - and ((C(CN))2NC(CF3))N - anions in .

6. The secondary battery according to claim 1, wherein The lithium salt contains Li + As a cation, and containing BF4 - , B 10 Cl 10 - 、ClO4 - 、AlO4 - 、AlCl4 - PF6 - 、SbF6 - 、AsF6 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、(C2O4)2PF2 - ,CF3SO3 - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - and SCN - At least two anions in the 7. The secondary battery according to claim 1, wherein The non-aqueous organic solvent further includes at least one co-solvent selected from the group consisting of fluorinated ether solvents, fluorinated cyclic carbonate solvents, chain carbonate solvents, phosphate / ester solvents, and sulfone solvents.

8. The secondary battery according to claim 1, wherein The electrolyte composition further comprises an electrolyte additive represented by Formula 3: [Formula 3] Among them, R1 represents R1’ and R1” independently represent hydrogen or methyl, R2 includes at least one of the following: an arylene group having 6 to 20 carbon atoms; an aryloxy group having 6 to 20 carbon atoms; a heteroarylene group having 5 to 10 carbon atoms and at least one heteroatom among N, S and O; a heteroaryloxy group having 5 to 10 carbon atoms and at least one heteroatom among N, S and O; an alkyl group having 1 to 10 carbon atoms; an alkyloxy group having 1 to 10 carbon atoms; a cycloalkyl group having 5 to 10 carbon atoms; and R3 represents a fluoro group, an alkyl group having 1 to 10 carbon atoms, an alkyloxy group having 1 to 10 carbon atoms, or Provided that the alkyl, alkyloxy, cycloalkyl, and At least one hydrogen atom contained in may be replaced by a fluorine atom, M includes at least one selected from the group consisting of lithium, sodium, potassium, tetraalkylammonium having 1 to 4 carbon atoms, and tetraalkylphosphonium having 1 to 4 carbon atoms, l is an integer from 1 to 6, and m and n are each independently an integer from 2 to 20.

9. The secondary battery according to claim 8, wherein: The electrolyte additive represented by Formula 3 contains one or more of the compounds represented by the following structural formulas 1 to 17:

10. The secondary battery according to claim 8, wherein Based on the total weight of the electrolyte composition, the content of the electrolyte additive is 5% by weight or less.

11. The secondary battery according to claim 1, wherein The negative electrode has a negative electrode active layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active layer comprises a carbon-based negative electrode active material and a silicon-based negative electrode active material, and The carbon-based negative electrode active material comprises at least one carbon material selected from natural graphite, artificial graphite, expanded graphite, hard carbon, acetylene black, and Ketjen black.

12. The secondary battery according to claim 11, wherein The silicon-based negative electrode active material comprises silicon (Si), silicon carbide (SiC), silicon oxide SiO q At least one of the following, wherein 0.8≤q≤2.

5.

13. The secondary battery according to claim 11, wherein Based on the total weight of the negative electrode active material, the content of the silicon-based negative electrode active material is 0.1% by weight to 30% by weight.

14. A method for manufacturing a secondary battery, the method comprising: Preparing an electrode assembly, the electrode assembly comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; And Impregnating the electrode assembly in an electrolyte composition, Wherein, the positive electrode has a positive electrode active layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active layer contains a lithium metal oxide represented by Formula 1 as a positive electrode active material; Among them, the electrolyte composition contains a lithium salt and a non-aqueous organic solvent. Based on the total weight of the non-aqueous organic solvent, the non-aqueous organic solvent contains more than 60% by weight of a cyclic ester solvent represented by Formula 2; Among them, when measuring the heat flow of a mixture of the positive electrode active material and the electrolyte composition in a 100% charged state with a weight ratio of 1:1, the heat flow measured in the temperature range of 200 °C to 300 °C is 6.0 W / g or less; [Formula 1] Li x [Ni y Co z Mr w M 1 v ]O2 [Formula 2] In Formula 1 and Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, x, y, z, w, and v respectively satisfy 0.9 ≤ x ≤ 1.30, 0.6 ≤ y < 1, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and 0 ≤ v ≤ 0.1, provided that y + z + w + v = 1, represents a single bond or a double bond, X is hydrogen, fluorine, or vinyl; and p is an integer from 1 to 5.

Citation Information

Patent Citations

  • Organic additive coating method for improving interfacial stability of cathode material for lithium secondary battery

    KR1020180116564A

  • Acid purification of carbon nanotubes

    KR1020230080465A

  • A cathode active material, method of preparing the same, and lithium secondary battery comprising a cathode comprising the cathode active material

    KR102144056B1